Seasonal Variation of Thermocline Depth: Consequence on Nutrient Availability in the Ivorian Coastal Zone - Jean-Baptiste, Kassi Ahon; Herve, Mobio Abaka Brice; Jeanne, Kouadio Maffoue; Andre, Tiemele Jacques (European Scientific Journal, ESJ, 2017)
Faced with the threat of overfishing in Africa, this study was initiated in the coastal zone of CÃ´te d’Ivoire to understand the nutrients availability as function of variation in the depth of thermocline. Data from the ocean bank, World Ocean Atlas (WOA), were used in the ODV software during the twelve months of 2009 taken at 5.5Â°W/4.5Â°N (station coordinates). ODV software has allowed to make seasonal analysis, from vertical profiles and latitudinal analysis from the coast toward the sea through some parameters such as temperature, nitrate, phosphate and oxygen. The depth of thermocline, nitracline, phosphacline and oxycline was determined by the seasonal analysis. To evaluate the enrichment intensity of coast towards the sea, latitudinal analysis was investigated using the section profiles (1Â°S/5Â°N coordinates). The main results have shown not only the variation in the depth of the thermocline, but also the variation of nitracline, phosphacline and oxycline at different marine seasons. During the cold season, there was an ascent of the thermocline over the surface of water and a strong enrichment from the coast to the sea especially in August. While in hot season, the thermocline was lower and its stability has favoured the stratification of the water column, which prevents the enrichment of the oxygenated surface layer. Analysis of relationships shows that nutrient elements and oxygen change polynomially with temperature.